Gender and corporate boards - Brown, Scarlett. (New York, NY)
1 online resource (165 p.).
Keywords: The lack of women on boards has galvanised much public and policy interest, which has led to many countries introducing quotas for women on boards, or to concerted voluntary action. However the way that directors are appointed remains opaque and prone to the influence of gender. Using a social constructionist understanding of gender and a discourse analysis, Gender and Corporate Boards explores the board appointment process through the experiences of women and men seeking non-executive board roles. The book is unique in that it traces board-ready candidates, who have been vetted by an executive search firm, over an 18-month period. By taking a longitudinal and prospective view rather than retrospective and snapshot, it provides deep analysis of how the board appointment process is gendered. This volume privileges the voices of those who are seeking board roles to show how they make sense of an unpredictable and complex process. Gender and Corporate Boards first analyses how aspirant board candidates see themselves in relation to the market, through exploring their perceptions of the ideal board member and how they position themselves towards this ideal. Second, the book shows how candidates must leverage their networks to get board appointments, and that the process is gendered: women and men receive different benefits from their networks. Third, the book explores how the participants make sense of success and failure and how their justifications are also gendered. The book will be of interest to those seeking to understand dynamics of gender on boards as well as those interested in gender and leadership more broadly.